Uji Konsentrasi Metabolit Sekunder Bakteri Bacillus sp. terhadap Jamur Colletotrichum sp. Pada Benih Cabai Rawit Metode Blotter Test - Nurul Afida; Arika Purnawati; Tri Mujoko (Vegetalika, 2025)
Low-quality seeds can negatively affect the success of agricultural practices by reducing yield and increasing susceptibility to pathogen infection. Pathogens may infect seeds starting from the field, during transportation, and throughout storage. The utilization of Bacillus sp. as a biological control agent has been extensively studied due to its ability to produce secondary metabolites with antifungal properties. This study aimed to determine the effective concentration level of secondary metabolites of Bacillus sp. Bth-22 in suppressing Colletotrichum sp. infection on chili pepper (Capsicum frutescens L.) seeds using the blotter test method. The experiment was arranged in a completely randomized design (CRD) with a single factor consisting of concentration levels (10%, 15%, 20%, 25%, and 30%), sterile distilled water, and the chemical fungicide propineb as controls. The results showed that treatment with various concentrations of secondary metabolites of Bacillus sp. Bth-22 significantly affected the infection level, with concentrations of 30% (G) at 36%; 25% (F) and KP (B) at 38.6%; 20% (E) at 40%; 15% (D) at 42.6%; and 10% (C) at 44%, compared with the negative control. In addition, treatments also suppressed infection levels, with 30% (G) at 43.3%; 25% (F) and KP (B) at 39.3%; 20% (E) at 37%; 15% (D) at 33.6%; and 10% (C) at 31%. Furthermore, application of Bacillus sp. Bth-22 secondary metabolites induced abnormalities in fungal hyphae, such as curling, twisting, and bending, indicating antifungal activity of the bioactive compounds produced by Bacillus sp. Bth-22.